2012
DOI: 10.1007/s11999-011-2176-4
|View full text |Cite
|
Sign up to set email alerts
|

The Natural History of Idiopathic Frozen Shoulder: A 2- to 27-year Followup Study

Abstract: Background The natural history of spontaneous idiopathic frozen shoulder is controversial. Many studies claim that complete resolution is not inevitable. Based on the 40-year clinical experience of the senior author, we believed most patients with idiopathic frozen shoulder might have a higher rate of resolution than earlier thought. Questions/purposes We determined the length of symptoms, whether spontaneous frozen shoulder recovered without any treatment, and whether restored ROM, pain relief, and function p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
119
0
7

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(130 citation statements)
references
References 17 publications
4
119
0
7
Order By: Relevance
“…Duration of the disease averaged 15 months in untreated group. 15 While this study showed the improvement in the restricted abduction ROM in a shorter period of time using a combination of Kaltenborn and ROM exercises.…”
Section: Resultsmentioning
confidence: 64%
“…Duration of the disease averaged 15 months in untreated group. 15 While this study showed the improvement in the restricted abduction ROM in a shorter period of time using a combination of Kaltenborn and ROM exercises.…”
Section: Resultsmentioning
confidence: 64%
“…They concluded that adhesive capsulitis worsened the diabetics' quality of life. 18 The course of this disease is prolonged, 14,19 greatly impairing sleep and the patients' everyday activities and, therefore, their physical, psychological and social QoL as reflected in the various WHOQOL-BREF domains before SSNB treatment. Baums et al used the SF-36 to examine the QoL of adhesive capsulitis patients before surgical release and found that the physical component was considerably affected.…”
Section: Discussionmentioning
confidence: 99%
“…Vastamäki et al clearly showed that the length of symptoms and restriction of motion are shorter than originally described, and the focus of the present study was to specifically investigate the effect of a single corticosteroid injection in the symptomatic stage in patients with both pain and stiffness. 34 The inclusion of a placebo group would have been beneficial to investigate the effect of natural recovery and resolution of pain, but given the retrospective nature of the project, this was not possible. Finally, six experienced musculoskeletal physiotherapists assessed range of motion.…”
Section: Discussionmentioning
confidence: 99%